Examining fan participation in the digital media: Fans' transcreation of webtoons - Jinyoung Nam; Yoonhyuk Jung (International Telecommunications Society (ITS), 2021)
The rising popularity of webtoons, a popular type of digital content, led to emergence of an interesting phenomenon known as transcreation. Transcreation indicates fans' twofold activity of translating and recreating webtoons into a new language, while maintaining originality of the content. Although transcreators are playing a significant role in facilitating the spread of webtoons in the global market, the role of such transcreators has received scant attention. By employing the means-end chain approach through laddering interviews, the study explicates fans' goal structure in transcreation of webtoons. This empirical study provides insights into fans' involvement in the digital media industry.
Keywords: 330; Webtoon industry; Transcreation; Fandom; Fan participation; Digital media; Goal hierarchy; Means-end chain